Cognitive bias in voters' retrospective evaluations associated with COVID-19: evidence from Japan - Ohmura, Hanako (Frontiers in Social Psychology, 2024)
Retrospective voting studies on catastrophic disasters can entail cognitive biases and politically affected approval/disapproval toward the government. In this study, I conducted an online survey experiment to assess the impact of providing individuals with information about COVID-19 infection status on their attitudes toward the government, governor, local administration, and national/local economic policies (n = 2,975). The findings indicated that the group exposed to positive information regarding infection status demonstrated a higher likelihood of adopting positive attitudes, while the group exposed to negative information showed a higher likelihood of adopting negative attitudes, despite receiving no other information. Although it was expected that individuals residing in prefectures with regular appearances of the governor on mass media platforms and that obtained COVID-19-related funding from the government would have a greater likelihood of experiencing such an attitude change, the findings do not corroborate these hypotheses.